The usage of LMS among undergraduate students - Kung, Siew Min; Mat Yamin, Fadhilah; Wan Ishak, Wan Hussain (2012)
Learning Management System (LMS) is one of the knowledge management tools that support knowledge sharing and communication among its participants.LMS is one of the popular applications among institution of higher learning in Malaysia.This study empirically investigates the activities that students mostly participated while they are login to LMS.This study also investigates the impact of LMS on teaching and learning. Fifty respondents involved in this short survey.The findings are significant to LMS designers, providers and institution of higher learning that subscribe to the LMS.These findings will give some insight on how the students utilize LMS.